Age‐related changes in the coronary microcirculation influencing the diagnostic performance of invasive pressure‐based indices and long‐term patient prognosis. Issue 7 (23rd October 2022) - Faria, Daniel; Mejia‐Renteria, Hernan; Lee, Joo Myung; Lee, Seung Hun; Travieso, Alejandro; Jung, Ji‐Hyun; Doh, Joon‐Hyung; Nam, Chang‐Wook; Shin, Eun‐Seok; Hoshino, Masahiro; Sugiyama, Tomoyo; Kanaji, Yoshihisa; et al.
Abstract: Objectives: Investigate age‐related changes in coronary microvascular function, its effect on hyperemic and non‐hyperemic indices of stenosis relevance, and its prognostic implications. Background: Evidence assessing the effect of age on fractional flow reserve (FFR), resting mean distal intracoronary pressure/mean aortic pressure (Pd/Pa), and microcirculatory function remains scarce. Methods: This is a post hoc study of a large prospective international registry (NCT03690713) including 1134 patients (1326 vessels) with coronary stenoses interrogated with pressure and flow guidewires. Age‐dependent correlations with functional indices were analyzed. Prevalences of FFR, resting Pd/Pa, and coronary flow reserve (CFR) classification agreement were assessed. At 5 years follow‐up, the relation between resting Pd/Pa, CFR, and their age‐dependent implications on FFR‐guided percutaneous coronary intervention (PCI) deferral (deferred if FFR > 0.80) were investigated using vessel‐oriented composite outcomes (VOCO) composed of death, myocardial infarction, and repeated revascularization. Results: Age correlated positively with FFR ( r  = 0.08, 95% confidence interval [CI]: 0.03 to 0.13, p  =  0.005), but not with resting Pd/Pa ( r  = −0.03, 95% CI:−0.09 to 0.02, p  = 0.242). CFR correlated negatively with age ( r  = −0.15, 95% CI: −0.21 to −0.10, p  < 0.001) due to a significant decrease in maximal hyperemic flow in older patients. Patients over 60 years of age with FFR‐guided deferred‐PCI abnormal resting Pd/Pa or abnormal CFR had increased risk of VOCO (hazard ratio [HR]: 2.10, 95% CI: 1.15 to 4.36, p  = 0.048; HR: 2.46, 95% CI:1.23 to 4.96, p  = 0.011; respectively). Conlusions: Aging is associated with decrease in microcirculatory vasodilation, as assessed with adenosine‐based methods like CFR. In patients older than 60 years in whom PCI is deferred according to FFR > 0.80, CFR and resting Pd/Pa have an incremental value in predicting future vessel‐oriented patient outcomes.